2015
DOI: 10.1177/1059840515620841
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Consent Procedures, Participation Rates, and Main Findings of Health-Related Research in Alternative High Schools From 2010 to 2015

Abstract: There is a well-established link between educational attainment and health. Alternative high schools (AHSs) serve students who are at risk for school dropout. Health-related research conducted in AHSs has been sparse. Achieving high participation rates is critical to producing generalizable results and can be challenging in research with adolescents for reasons such as using active consent. These challenges become greater when working with vulnerable populations of adolescents. In this systematic review, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Three reviews indicate that substance use is often targeted in alternative schools even if they do not enroll youth with substance use disorders, and solely reducing substance use may not reduce HIV risk behaviors. 2326 Substance use at time of sex, however, can increase the risk of unprotected sex, but there were no differences between interventions. It is possible that a greater emphasis on substance use and additional skills to reduce substance use in sexual situations was needed.…”
Section: Discussionmentioning
confidence: 97%
“…Three reviews indicate that substance use is often targeted in alternative schools even if they do not enroll youth with substance use disorders, and solely reducing substance use may not reduce HIV risk behaviors. 2326 Substance use at time of sex, however, can increase the risk of unprotected sex, but there were no differences between interventions. It is possible that a greater emphasis on substance use and additional skills to reduce substance use in sexual situations was needed.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to facing these structural inequalities in our education system, AHS students face high levels of personal stressors. As compared to peers in traditional schools, AHS students more frequently experience adverse childhood experiences, homelessness, and living in unsafe and/or impoverished neighborhoods (Johnson, Morris, Rew, & Simonton, ). Consequently, AHS students experience higher levels of emotional and behavioral problems and are involved in high levels of health‐risk behaviors (Grunbaum et al., ; Johnson, McMorris, & Kubik, ); in other words, this is the population we most need to monitor to address disparities in adolescence that may progress throughout the life span and cost society billions of dollars.…”
Section: Alternative High Schools: Missing From Public Health Surveilmentioning
confidence: 99%
“…Researchers generally report response rates or cooperation rates but do not make it clear which rate they are reporting. In health‐related research in AHSs from 2010 to 2015, only 42% of articles reported student‐level participation rates (Johnson et al., ).…”
Section: Findings From Current Study and Lessons Learnedmentioning
confidence: 99%
“…Students attending alternative schools are much more likely than students attending mainstream schools to experience numerous health conditions (e.g., mental health issues, substance use, and violence) and health risk factors (e.g., homelessness and abuse). 6 In particular, girls attending alternative schools are at least twice as likely to report sexual behaviours: ever had sex (48% vs. 86%), sex within the past 3 months (35% vs. 66%), had at least four sex partners (16% vs. 48%), and used alcohol or drugs immediately prior to sex (25% vs. 43%). 5 Yet, compared with mainstream schools, few health interventions, and fewer STI prevention interventions, have been conducted within alternative schools.…”
mentioning
confidence: 99%
“…5 Yet, compared with mainstream schools, few health interventions, and fewer STI prevention interventions, have been conducted within alternative schools. 6 We developed an STI primary preventive intervention for adolescent girls attending an alternative disciplinary school (ages 16 to 18 years) that included activities designed to reduce girls' sexual partner risk measured with eight characteristics: age difference, history of jail, recency of sexually transmitted disease (STD), place where they met, drinking alcohol in the two-hours prior to sex, history of sex with men, recent sexual activity, and drug use in the two-hours prior to sex. These eight characteristics were chosen because of their high correlation with STI risk, especially when considered together, and their potential for modification.…”
mentioning
confidence: 99%